2023
DOI: 10.3389/fpsyt.2023.1119998
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Black and South Asian women’s experiences of help-seeking and engagement in perinatal mental health services in the UK

Abstract: Background and aimsIn the United Kingdom (UK), Black and South Asian women are less likely than White British women to access support from perinatal mental health services, despite experiencing similar, or higher, levels of distress. This inequality needs to be understood and remedied. The aim of this study was to answer two questions: how do Black and South Asian women experience (1) access to perinatal mental health services and (2) care received from perinatal mental health services?MethodSemi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…These findings should be considered alongside, and as complementary to, research exploring Black and South Asian women’s experiences of support from perinatal mental health services. This study found that women who did access services encountered complex interlayer barriers, and many struggled to access support from services despite repeated insistent attempts [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings should be considered alongside, and as complementary to, research exploring Black and South Asian women’s experiences of support from perinatal mental health services. This study found that women who did access services encountered complex interlayer barriers, and many struggled to access support from services despite repeated insistent attempts [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Coding recurring viewpoints; (4) Collecting coded views to nd common meaningful concepts and form preliminary themes; (5) Providing detailed descriptions of each theme generated in the previous step, and extracting the original statements from the interviewees; (6) Grouping similar themes and their descriptions for repeated comparison, discerning and extracting similar viewpoints, then constructing a concise and meaningful phrase, namely, the theme; (7) Returning the generated theme structure to the interviewees for validation, asking if it captures their real experience to ensure the accuracy of the results.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Research both domestically and internationally indicates that pregnant women, due to multiple pressures such as physiological changes and environmental adaptation, are more prone to mental health problems, yet they exhibit a de ciency in behaviors seeking professional psychological help [4]. Only about 12-35% of pregnant women will actively seek professional psychological help [4][5][6][7][8][9][10]. The lack of professional psychological help-seeking behavior not only affects their mental health but also impacts the development of the infant and the harmony of the family [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Black and south Asian women appeared to be less likely to seek help and engagement in perinatal mental health services in the UK than their while British counterparts, although they may have similar, or higher levels of mental distress. Themes of self-identity and social expectations deterred seeking help 43 . Services that were not clearly visible (hidden) or disorganized made getting support more di cult 44 .…”
Section: Access To Perinatal Services and Ethnicity In The Ukmentioning
confidence: 99%
“…Kindness, curiosity, and exibility in making women feel heard, accepted, and supported by clinicians was important 45 . Interestingly, a shared cultural background was noted to both support and be detrimental to building rapport and trust 43 .…”
Section: Access To Perinatal Services and Ethnicity In The Ukmentioning
confidence: 99%